2018
DOI: 10.1007/s40831-018-0198-9
|View full text |Cite
|
Sign up to set email alerts
|

An Ex-ante LCA Study of Rare Earth Extraction from NdFeB Magnet Scrap Using Molten Salt Electrolysis

Abstract: A new recycling process for the extraction of rare earths from neodymium-iron-boron (NdFeB) magnet scrap is being developed, based on the direct extraction of rare earths from end-of-life magnet material in a molten fluoride electrolysis bath. Rare earths are required in their metallic form for the production of new NdFeB magnets, and the suggested process achieves this through a single step. The process is being developed on a laboratory scale and has been proven to work in principle. It is expected to be env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Two studies mentioned that LCA experts had discussions with technology experts about what the hypothetical upscaled technologies would look like (Villares et al 2016;Schulze et al 2018). Muñoz (2019) developed a scenario of a hypothetical upscaled technology as follows (pers.…”
Section: Methodological Principles Of Upscaling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies mentioned that LCA experts had discussions with technology experts about what the hypothetical upscaled technologies would look like (Villares et al 2016;Schulze et al 2018). Muñoz (2019) developed a scenario of a hypothetical upscaled technology as follows (pers.…”
Section: Methodological Principles Of Upscaling Methodsmentioning
confidence: 99%
“…Proxies were used for data estimation in 7 out of 18 studies (Mattick et al 2015;Simon et al 2016;Villares et al 2016;Sampaio et al 2017;Salas et al 2018;Schulze et al 2018;Muñoz et al 2019). They retrieved proxy data from various sources, such as LCI databases (Muñoz et al 2019;Villares et al 2016), the literature and engineering case studies (Schulze et al 2018;Villares et al 2016), online catalogs of the machines (Sampaio et al 2017;Salas et al 2018), and expert consultation provided by technology developers (Simon et al 2016). Energy flows, material flows, and elementary flows of the new technologies were approximated by using data of a similar existing technology.…”
Section: Methodological Principles Of Upscaling Methodsmentioning
confidence: 99%
“…There are several ways to go about data estimation, for example, Cossutta et al (2017) and Mazzoni et al (2019) employed process simulations to estimate large-scale data flows of their emerging technologies. While Piccinno et al (2018) proposed the use of manual calculations to scale up their laboratorybased process, Villares et al (2016) and Schulze et al (2018) utilized the proxy method for the same purpose. Based on their literature review, Tsoy et al (2020) found that the accuracy of data estimation methods decreases from process simulation to manual calculations, to proxy data and data omission.…”
Section: Upscaling Of Foreground Systemsmentioning
confidence: 99%
“…Therefore, carrying out carbon footprint accounting of rare earth resource development is also essential for formulating low-carbon development strategies for the industry [17,18]. Current studies on carbon footprint in the field of rare earths are mainly from the product perspective, covering topics such as rare earth oxides [17], rare earth metals [19], and NdFeB (Neodymium Magnets) permanent magnet materials [11], and recycling processes, such as NdFeB scrap recycling [20] from the recycling technology perspective [12]. However, there are still knowledge gaps in the carbon footprint accounting of rare earth development, particularly from the life cycle assessment perspective.…”
Section: Introductionmentioning
confidence: 99%